Korelasi Kemampuan Memahami Ciri Pantun dan Kemampuan Menentukan Jenis Pantun dengan Kemampuan Menulis Pantun Siswa Kelas VIII SMP Negeri I Pagaralam - Chairil Amar (Universitas PGRI Palembang, 2016)
This study wants to answer about the correlation between the ability to understand the features and capabilities to determine what kind of rhymes with the ability to write rhymes of students in class VIII at SMP Negeri 1 Pagaralam. The purpose of this study was to describe the correlation between the ability to understand the features and capabilities to determine what kind of rhymes with the ability to write rhymes of students in class VIII at SMP Negeri 1 Pagaralam. This study used a descriptive and correlation method. The results of data analysis research concluded, that there is a significant correlation of the ability to understand the characteristics and capabilities to determine what kind of rhymes with the ability to write rhymes of students in class VIII SMP Negeri 1 Pagaralam. The hypothesis shown that there is a significant correlation between the understanding of the characteristics and capabilities to determine what kind of rhymes with the ability to write rhymes of students in class VIII at SMP Negeri 1 Pagaralam that proven true. Keywords: correlation, the characteristics of rhyme, rhyme types, writing rhymes.